A Comprehensive Analysis of Supervised Learning Techniques for Electricity Theft Detection - Bohani F.A.; Suliman A.; Saripuddin M.; Sameon S.S.; Md Salleh N.S.; Nazeri S. (Hindawi Limited, 2023)
Adaptive boosting; Crime; Decision trees; Deep neural networks; Neural networks; Supervised learning; Comparative studies; Comprehensive analysis; Electricity theft detection; Future research directions; Learning classifiers; Pre-processing method; Predictive accuracy; Supervised learning methods; Learning systems